Religious Life: A Preliminary Literature Review - Mohamad, alimahtul Sa’diyah; Awang, Jaffary (International Journal of Psychosocial Rehabilitation, 2020)
Religious life is a quintessential spectrum of universal human life regardless of the age, race, religion and position that is imperative in a religious person’s life in interpreting religion based on one’s belief in a religion practised daily. The conclusions confirmed that practising a religious life can guide a person’s thoughts, feelings and actions to his or her religious beliefs and make everything happen based on God’s willing by accepting the difference in religious life to the diversity of beliefs that exist in the community whether they believe the existence of God, no God and no religion depends on the individual’s beliefs. To bring about religious life in the context of universal, religious institutions must play a position in raising awareness of the importance of religious life and presenting religious understanding and practice with the religion embraced.